2013
DOI: 10.1007/s00394-013-0560-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and neurodevelopment in children: focus on NUTRIMENTHE project

Abstract: There is growing evidence that early nutrition affects later cognitive performance. The idea that the diet of mothers, infants, and children could affect later mental performance has major implications for public health practice and policy development and for our understanding of human biology as well as for food product development, economic progress, and future wealth creation. To date, however, much of the evidence is from animal, retrospective studies and short-term nutritional intervention studies in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 163 publications
0
74
0
3
Order By: Relevance
“…It is possible that mothers with higher socioeconomic status during pregnancy may consume a more nutrient-rich diet. It has been shown that maternal nutritional status in pregnancy can influence fetal brain development, and it is possible that a similar mechanistic model is occurring within our cohort and potentially influencing our results (26). It is worth noting that other studies have found significant positive associations that were contrary to their a priori hypotheses with regard to organophosphate pesticides and neurodevelopment in infants and young children (6,27).…”
Section: Discussionmentioning
confidence: 59%
“…It is possible that mothers with higher socioeconomic status during pregnancy may consume a more nutrient-rich diet. It has been shown that maternal nutritional status in pregnancy can influence fetal brain development, and it is possible that a similar mechanistic model is occurring within our cohort and potentially influencing our results (26). It is worth noting that other studies have found significant positive associations that were contrary to their a priori hypotheses with regard to organophosphate pesticides and neurodevelopment in infants and young children (6,27).…”
Section: Discussionmentioning
confidence: 59%
“…Not only does folate restriction affect neural tube closure, but folate and related B-vitamins are thought to be fundamental in regulating later neurodevelopment [37][38][39]. However, evidence in the literature is sparse with regard to the effects on specific areas of brain function, such as cognition, motor skills and memory [40] with the majority of evidence existing from observational and animal studies.…”
Section: Benefits or Not Of Folic Acid In Later Brain Developmentmentioning
confidence: 99%
“…22 Third, vitamin B 12 contributes to DNA methylation and epinephrine synthesis, along with methionine synthesis. 21,23 Fourth, zinc is important for neuron formation, migration, and synapse generation, 24 and, if given as a supplement, can reduce the risk of preterm birth. 25 Fifth, tryptophan is an essential amino acid needed for the formation of neurotransmitters.…”
Section: The Impact Of Preconception and Prenatal Maternal Nutritionmentioning
confidence: 99%